Well productivity handbook : vertical, fractured, horizontal, multilateral, multi-fractured, and radial-fractured wells - Guo, Boyun (Gulf Professional Publishing, 2019)
Well Productivity Handbook: Vertical, Fractured, Horizontal, Multilateral, Multi-fractured, and Radial-Fractured Wells, Second Edition delivers updated examples and solutions for oil and gas well management projects. Starting with the estimation of fluid and reservoir properties, the content then discusses the modeling of inflow performance in wells producing different types of fluids. In addition, it describes the principle of well productivity analysis to show how to predict productivity of wells with simple trajectories. Then advancing into more complex trajectories, this new edition demonstrates how to predict productivity for more challenging wells, such as multi-lateral, multi-fractured and radial-fractured. Rounding out with sample problems to solve and future references to pursue, this book continues to give reservoir and production engineers the tools needed to tackle the full spectrum of completion types. -- Provided by publisher.
Part I: Well Productivity Basics 1. Introduction 2. Petroleum Reservoir Properties 3. Reservoir Deliverability 4. Wellbore Performance 5. Productivities of Wells with Conventional Completions Part II: Productivity of Multi-Lateral Wells 6. Productivity of Wells with Simple Completions 7. Productivity of Multi-Fractured Horizontal Wells 8. Productivity of Radial-Fractured Wells Appendix A. Unit Conversion Factors B. Minimum Performance Properties of API Tubing C. Mathematical Model for Obtaining Oil Rate Correction Factor FO D. Mathematical Model for Obtaining Oil Rate Correction Factor FG
Keywords: Oil wells.; Gas wells.; Oil reservoir engineering.; Gas reservoirs.; Petroleum engineering.; Industrial productivity.; elektronické knihy; electronic books